Diseño en CFD del alerón delantero de un vehículo fórmula SAE (2017)
"This thesis presents the front wing design in CFD (Computational Fluid Dynamics), in 2D and 3D. An adequate aerodynamic profile is obtained, the dimensional parameters are changed in order to find the optimal geometry, and 3D simulations are done to visualize the wake generated and to verify the obtained geometry that allows to maximize the lift coefficient CL, while keeping the drag coefficient CD in the calculated range, and justifying the front wing's inclusion in the vehicle's aerodynamic package." -- Tomado del Formato de Documento de Grado.